The mediating effect of personal mastery and perceived social support between emotional intelligence and social alienation among patients receiving peritoneal dialysis - Keke Diao; Keke Diao; Jiajia Wang; Yanjun Zhang; Yijia Huang; Yan Shan (Frontiers Media S.A., 2024)
AimThis study aims to assess the extent of social alienation in patients undergoing peritoneal dialysis and examine how personal mastery and perceived social support mediate the association between emotional intelligence and social alienation in this patient population.MethodsThis study adopts a cross-sectional survey design. A total of 192 patients were recruited from a tertiary hospital located in Henan Province, China, using a convenience sampling method. We have developed a structural equation model to investigate the mediating influence of personal mastery and perceived social support on the emotional intelligence and social alienation of patients undergoing Peritoneal dialysis.ResultsPeritoneal patients exhibited an social alienation score of 42.01 ± 3.15. Elevated EI levels (coefficient = −0.616, p < 0.001) were significantly correlated with reduced social alienation. The mediation model demonstrated that personal mastery and perceived social support fully mediated the impact of emotional intelligence on social alienation.ConclusionThe social alienation of peritoneal dialysis patients is serious, and healthcare professionals should pay attention to patients' social alienation, improve patients' emotional intelligence through relevant interventions, increase personal mastery and perceived social support, and finally reduce social alienation.